To find the solution to this system of equations, you can set the two equations equal to each other, since they both equal y.
Therefore, -x + 3 = -2x + 6.
To solve for x, you would first subtract -x from both sides:
3 = -x + 6.
Then subtract 6 from both sides to isolate x:
-3 = -x.
Finally, multiplying by (-1) on both sides, we get:
3 = x
Therefore x = 3.
To find y, substitute x back into one of the equations, for example, y = -2(3) + 6 = 0.
Thus, the solution to this system of equations is x = 3 and y = 0.
what is the solution of
y = -x + 3
y= -2x + 6
1 answer